Urban heat island in barrios de Arboledas neighborhoods of Puebla, Mexico: an analysis of its causes - González Meza, Cynthia; Santiago Azpiazu, Gloria Carola; Guevara Romero, María Lourdes; Mundo Hernández, Julia Judith (Estoa. Journal of the Faculty of Architecture and Urbanism, 2026)
Currently, humanity is facing complicated environmental challenges due to Climate Change and Urban Heat Island (UHI) effects. This research is conducted in the Barrios de Arboledas neighborhood in Puebla, Mexico. The aim is identifying the causes of UHI at the neighborhood level and developing mitigation strategies based on building sustainability competencies among residents. The study began with a site analysis to identify the causes and factors associated with UHI through residents´ surveys and photographic and geospatial information. Results indicate that the presence of air pollution, the use of low-albedo materials, the reduction of green areas, and anthropogenic heat are causing UHI. As mitigation strategies, government programs for waste management were implemented, along with workshops and sociocultural activities to raise environmental awareness.